Influence of quaternization of ammonium on antibacterial activity and cytocompatibility of thin copolymer layers on titanium. Issue 15 (12th October 2016) - Waßmann, Marco; Winkel, Andreas; Haak, Katharina; Dempwolf, Wibke; Stiesch, Meike; Menzel, Henning
Abstract: Antimicrobial coatings are able to improve the osseointegration of dental implants. Copolymers are promising materials for such applications due to their combined properties of two different monomers. To investigate the influence of different monomer mixtures, we have been synthesized copolymers of dimethyl (methacryloxyethyl) phosphonate (DMMEP) and dipicolyl aminoethyl methacrylate in different compositions and have them characterized to obtain the r -parameters. Some of the copolymers with different compositions have also been alkylated with 1-bromohexane, resulting in quaternized ammonium groups. The copolymers have been deposited onto titanium surfaces resulting in ultrathin, covalently bound layers. These layers have been characterized by water contact angle measurements and ellipsometry. The influence of quaternary ammonium groups on antibacterial properties and cytocompatibility was studied: Activity against bacteria was tested with a gram positive Staphylococcus aureus strain. Cytocompatibility was tested with a modified LDH assay after 24 and 72 h to investigate adhesion and proliferation of human fibroblast cells on modified surfaces. The copolymer with the highest content of DMMEP showed a good reduction of S. aureus and in the alkylated version a very good reduction of about 95%. On the other hand, poor cytocompatibility is observed. However, our results show that this trend cannot be generalized for this copolymer system.